GNCH-1: a high yielding, wilt and leafhopper resistant castor hybrid suitable for Gujarat: GNCH-1: A HIGH YIELDING, WILT AND LEAFHOPPER RESISTANT CASTOR HYBRID FOR GUJARAT - R S BHAKTA; V A LODAM; D A CHAUHAN; D A PATEL; V M PATEL; C G INTWALA; R B ARDESHNA; H P PATEL; S N GAJJAR; P DURAIMURUGAN; C LAVANYA; M SANTHA LAKSHMI PRASAD (Journal of Oilseeds Research, 2018)
GNCH-1 a high yielding, wilt and leafhopper resistant castor hybrid was developed by Pulses and Castor ResearchStation, Navsari Agricultural University,Navsari, Gujarat and released byCentral Sub-Committee onCrop Standards, Notification and Release (CVRC) of Variety for Agricultural Crops in 2017 for commercial cultivation under irrigated situation of Gujarat State, India. The hybrid GNCH-1 was developed by crossing a pistillate line SKP-84 with a male line DCS-94. On an average of 18 trials conducted for five years in south and middle Gujarat, the hybrid GNCH-1 recorded a seed yield of 2545 kg/ha which is 13.8, 35.9 and 31.0 per cent higher yield over the checks GCH-7, DCH-519 and DCH-177, respectively. The hybrid had long primary spike (64.8 cm), more numbers of capsules per primary spike (78.4), matures within 110-112 days and medium height (70-80 cm) which makes it suitable for easy harvesting. The oil content of the hybrid GNCH-1 (47.0 to 48.0 %) revealed that it is at par with the checks. The hybrid screened for wilt at national wilt sick plots showed resistance reactions (< 20%) to wilt. GNCH-1 screened against leafhopper using infester row method during 2014-17 showed resistant reaction to leafhopper (hopper burn grade 0 to 1 on 0-4 scale). The hybrid demonstrated in the farmers fields for two years (2016-18) showed higher seed yield than the existing cultivars. Due to plasticity for sowing time, this new hybrid is a suitable choice for the farmers of south and middle Gujarat under irrigated condition during late kharif and rabi seasons and paddy based cropping system.